Oxidatively generated damage to DNA: mechanistic aspects and formation in cells - Cadet, Jean (Henry Stewart Talks, 2020)
Oxidative stress and cellular oxidants, Nucleobase degradation pathways induced by hydroxyl radical, singlet oxygen and one-electron oxidants, Oxidatively generated damage to cellular DNA: single and tandem lesions, Epigenetic marks: enzymatic oxidation of 5-methycytosine, Measurement of oxidized bases: chromatographic and enzymatic assays, Base oxidation products formed in cellular DNA upon exposure to ionizing radiations and UVA component of solar light